POGLED V JEZIK IN IZ JEZIKA: ADI VIDOVIČ MUHA OB JUBILEJU. Ur. Mira Krajnc Ivič, Andreja Žele: Maribor: Univerzitetna založba Univerze, 2020. (Mednarodna knjižna zbirka Zora, 133). 272 str. - Žele, Andreja; Krajnc Ivič, Mira (Slavia Centralis, 2020)
The authors of the article give a brief overview of individual articles in the scientific monograph Pogled v jezik in iz jezika, dedicated to Ada Vidovič Muha on her eightieth birthday.
Keywords: Ada Vidovič Muha; scientific monograph; Pogled v jezik in iz jezika; review; eightieth birthday